Country risk in Greece, Spain and Turkey: Measurement and Policy Implications – an Application of the Fink Country Scoring Model - Haiss, Peter; Schicklgruber, Bernd (Видавництво Львівської політехніки, 2013)
Rising public deficits and debt levels, uneven growth and productivity and growing mistrust in official data in the Southern periphery of the Euro zone put downward pressure on the euro and confront policy makers with ambitious challenges. We examine the present situation in detail and apply the adapted Fink Country Scoring Model to assess and project the country risk of Greece, Spain and Turkey to compare factors of risk in and outside the Euro zone. Based on this purely economic model, we provide a less subjective, alternative view to country ratings by rating agencies. We find that Greece and Spain have envisaged pronounced worsening in their country risk throughout the past decade, while Turkey’s assessment improved. The projections indicate recovery for Spain, stabilization at a lower level for Greece and current account deficits increasing risk for Turkey. On a country-by-country basis, we derive economic policy implications and suggest restructuring with regard to budgetary consolidation, debt reduction, stimulation of competitiveness and enhanced transparency.
Keywords: Country risk; debt burden; rating; scoring model; Southern Europe